2014
DOI: 10.1002/ana.24027
|View full text |Cite
|
Sign up to set email alerts
|

Glial localization of antiquitin: Implications for pyridoxine‐dependent epilepsy

Abstract: Objective A high incidence of structural brain abnormalities has been reported in individuals with pyridoxine-dependent epilepsy (PDE). PDE is caused by mutations in ALDH7A1, also known as antiquitin. How antiquitin dysfunction leads to cerebral dysgenesis is unknown. In this study, we analyzed tissue from a child with PDE as well as control human and murine brain to determine the normal distribution of antiquitin, its distribution in PDE, and associated brain malformations. Methods Formalin-fixed human brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 46 publications
(124 reference statements)
3
45
0
Order By: Relevance
“…Past studies have identified possible structural brain defects in individuals with PDE [11,41]. In addition, several subjects in our study showed radiological evidence of brain injury likely caused by the seizures, and possibly the metabolic disturbances such as hypoglycemia, prior to diagnosis.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Past studies have identified possible structural brain defects in individuals with PDE [11,41]. In addition, several subjects in our study showed radiological evidence of brain injury likely caused by the seizures, and possibly the metabolic disturbances such as hypoglycemia, prior to diagnosis.…”
Section: Discussionsupporting
confidence: 53%
“…Subjects 2 and 5 had mesial temporal sclerosis with hippocampal injury, and both subjects had memory and concentration impairments [42,43]. Hippocampal sclerosis is most commonly associated with chronic epilepsy and has been associated with temporal lobe epilepsy and a history of febrile seizures [44,45], although it has been infrequently reported in subjects with PDE [41]. These observations link persisting neurologic dysfunction to brain damage occurring prior to the initiation of triple therapy, either the acute neurologic findings in subject 1 or the mesial sclerosis in subjects 2 and 5.…”
Section: Discussionmentioning
confidence: 99%
“…In three studies with a total of 44 patients with PDE, normal MRIs were seen in 20-31%. There have been two postmortem neuropathological studies of confirmed PDE [14,15]. Jansen et al reported severe dyslamination of the cortex with microcolumnar focal cortical dysplasia in resected tissue following right occipital and posterior parietal lobectomy at 15 months.…”
Section: Discussionmentioning
confidence: 99%
“…The Consortium recognizes that, aside from potential neurotoxic damage, the ID seen in PDE could be explained by the role of ATQ in neuronal migration (Jansen et al 2013), as well as the increased rate of fetal distress leading to premature birth and/or associated pathology (Mills et al 2010). Additionally, an association between delay in diagnosis and poor development has been reported (Bok et al 2012).…”
Section: Discussionmentioning
confidence: 99%